A internet e a prática da leitura: o uso da rede por acadêmicos do sexto período do curso superior em Tecnologia em Alimentos - Gnoatto, Marinês Augusta Zanatta [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Nowadays, the information is present in different means of communication, including technological means, and the human being is the only one capable not only to recreate symbols to communicate, as he is gifted, but also, of capacity to adapt himself to the technological innovations. In the western cultures seat in the internet logic, the support transformations, as well the techniques of text production in languages (verbal and not verbal), contributing to a gradual establishment of new ways to read. The internet passes to be seen as an information source more present in the persons day to day. To think, in this mean, is to think of the navigator subject as the reader subject. I tried to understand, in this research, as the students of the Higher Education in Technology seek and read information found in the internet for the production of academic papers. I performed an exploratory research, having questionnaires and semistructured interviews as tools for data collection. The research was anchored in studies of Bakhtin, Marcuschi, Chartier, Santaella, Lévy, Castells, Tamaél, Bajard, Foucambert. The Project was developed with 6th grade students of the Higher Education of Technology in Feed of the Universidade Tecnológica Federal do Paraná, Câmpus Medianeira. The analyzed data showed that not only the changes occurred in the way of to actualize the academic research, as demonstrated their reflexive behavior with relation to the contents found and extracted from the net. Therefore, as navigators have basic capacities to use the technologies, it was possible to notice, in these students, positive changes in relation to the reading in the digital means. With Access to the information in these means, they started to read more, to diversify the read subjects and to worry about the quantity and with the quality of the found material in the internet, so getting in a general way, to evaluate the information sources. I concluded that it is...

As informações, atualmente, circulam em diferentes meios de comunicação, inclusive em meios tecnológicos, e o ser humano é o único capaz de, não apenas (re) criar símbolos para comunicar-se, como é dotado, também, de capacidade para adaptar-se às inovações tecnológicas. Nas culturas ocidentais assentadas na lógica da internet, presenciam-se transformações do suporte, assim como da técnica de produção textual em linguagens (verbais e não verbais), contribuindo para uma gradual instauração de novas maneiras de ler. A internet passa a ser vista como a fonte de informação mais presente no dia a dia das pessoas. Pensar, neste meio, é pensar no sujeito navegador como sujeito leitor. Procurei compreender, neste trabalho, como os estudantes do ensino superior de Tecnologia buscam e leem informações encontradas na internet para a produção de trabalhos acadêmicos. Realizei uma pesquisa exploratória, tendo como instrumentos de coleta de dados questionários e entrevistas semiestruturadas. A pesquisa foi ancorada nos estudos de Bakhtin, Marcuschi, Chartier, Santaella, Lévy, Castells, Tamaél, Bajard, Foucambert. O projeto foi desenvolvido com estudantes do sexto período do Curso Superior de Tecnologia em Alimentos da Universidade Tecnológica Federal do Paraná, Câmpus Medianeira. Os dados analisados revelaram não apenas mudanças ocorridas na maneira de efetuarem as pesquisas acadêmicas, como demonstraram seu comportamento reflexivo com relação aos conteúdos encontrados e extraídos da rede. Como, porém, navegadores possuem capacidades básicas no uso das tecnologias, foi possível notar, nesses estudantes, mudanças positivas em relação à leitura nos meios digitais. Com acesso às informações nesses meios, passaram a ler mais, a diversificar os assuntos lidos e a preocupar-se com a quantidade e com a qualidade do material encontrado na internet, conseguindo assim, de um modo geral, avaliar as fontes de...
Keywords: Educação; Leitura; Internet na educação; Tecnologia educacional